Anti-inflammatory role of papaya seed extracts in inhibiting osteoclastogenesis of rats with Periodontitis - Ratih Pusporini; Ahmad Basori; Agung Krismariono (Faculty of Dentistry, Universitas Gadjah Mada, 2018)
Some previous studies mentioned that papaya seed extract has anti-inflammatory activity because it contains polyphenols including phenolic and flavonoid acids. Polyphenols of the papaya seed extracts are known to inhibit the severity of periodontitis. It can prevent the release of excessive osteoclastogenesis which may promote bone resorption aggravating periodontitis. Hence, this study aims to determine the role of papaya seed extract in reducing the number of osteoclasts in rats with periodontitis. Twenty-eight male Wistar rats were divided into 4 groups of induced periodontitis using lipopolisakarida (LPS) Porphyromonas gingivalis (P. Gingivalis) and followed by wire ligature in “8” placed around the mandible mandibular incisor. The first group was given standard food without any papaya extract, while each rat in three other groups with periodontitis (P2, P3, P4) was given with Papaya seed extracts of 200 mg/kgBW, 300 mg/kgBW, and 400 mg/kgBW. Seven rats in one group were not induced by periodontitis and were fed with standard food as a control group. On the 30th day, the rat was sacrificed, and its transverse pieces of alveolar bone around the mandibular incisor were stained with Hematoxylin-Eosin. The data analyzed by one way ANOVA indicated a significant result. Thus, it is conclusive that extract of papaya seed ethanol inhibited osteoclastogenesis in Wistar rats induced with periodontitis.